Kinetics of Hydrogen Evolution on Copper Electrode Involving Organic Acids as Proton Donors - Survila, A.; Kanapeckaitė, S.; Pileckienė, J.; Būdienė, J. (International Journal of Electrochemistry, 2011)
Linear potential sweep (LPS) voltammetry was applied to study the kinetics of hydrogen evolution in solutions containing glycolic, malic, tartaric, and gluconic acids. The CE mechanism of hydrogen evolution was analyzed invoking the 2nd Fick's law equations supplemented by terms that account for chemical interactions between diffusing particles. Acids are considered as components that are capable of releasing hydrated protons taking part in the charge-transfer step. Current peaks observed on LPS voltammograms are in linear dependence on ν (ν is the potential sweep rate). They obey well-known relationships obtained for simple redox processes, provided that the concentration of oxidant is treated as total concentration of proton donors. Determination of surface concentrations as current density functions makes it possible to transform LPS voltammograms into linear Tafel plots normalized with respect to the surface concentration of hydronium ions. Similar kinetic parameters (α≈0.6 and i0≈ 10 μA cm−2) obtained at pH 3 for all OA solutions indicate that the nature of OA has no noticeable influence on the charge-transfer process.